2022
DOI: 10.1186/s12889-022-13343-1
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset neonatal sepsis and antibiotic use in Indonesia: a descriptive, cross-sectional study

Abstract: Background Early diagnosis and prompt antibiotic treatment are crucial to reducing morbidity and mortality of early-onset sepsis (EOS) in neonates. However, this strategy remains challenging due to non-specific clinical findings and limited facilities. Inappropriate antibiotics use is associated with ineffective therapy and adverse outcomes. This study aims to determine the characteristics of EOS and use of antibiotics in the neonatal-intensive care units (NICUs) in Indonesia, informing efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
1
9
2
2
Order By: Relevance
“…Women with preterm infants had higher odds of developing breast problems compared to mothers with term infants. This finding is supported by a study conducted in Texas 27 . This difference might be due to restrictions on mother-infant continuous contact in neonatal intensive care units, as well as delays in discharge and limited contact with the mother after overcoming complications such as intraventricular hemorrhage and necrotizing enterocolitis.…”
Section: Discussionsupporting
confidence: 75%
“…Women with preterm infants had higher odds of developing breast problems compared to mothers with term infants. This finding is supported by a study conducted in Texas 27 . This difference might be due to restrictions on mother-infant continuous contact in neonatal intensive care units, as well as delays in discharge and limited contact with the mother after overcoming complications such as intraventricular hemorrhage and necrotizing enterocolitis.…”
Section: Discussionsupporting
confidence: 75%
“…This conclusion was consistent with a study conducted in Dil Chora Referral Hospital, Eastern, Ethiopia [ 32 ]and South Sinai, Egypt [ 33 ] which found that the prevalence of early onset neonatal sepsis in neonatal intensive care units was 40.5% and 31.8% respectively. Early onset neonatal sepsis (EONS) was found to be higher than studies conducted in Indonesia 26.6% [ 34 ] and in India 20.9% [ 35 ], in hospitals of Wolaita Sodo Town 26.9% [ 36 ]. The primary cause of the disparity could be differences in sociodemographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interpreting the clinical significance of these isolates can be challenging for physicians [27]. In contrast, Gram-negative bacteria were the predominant organisms isolated in similar studies elsewhere in South Asia [4,28]. Furthermore, Gram-negative infections have been associated with significantly greater morbidity and mortality in neonates and widespread AMR [4].…”
Section: Discussionmentioning
confidence: 99%